Implementasi Extreme Programming (Xp) dalam Pembuatan Sistem Informasi PTSL Berbasis Website Menggunakan Laravel Dengan Integrasi Peta Digital GIS (Studi Kasus: Desa Bukur) - Dewi, Alivia Prasetya; Ansor, Mohamad Khoirul; Kartika, Yayak (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Complete Systematic Land Registration (PTSL) is a government program to provide legal certainty and protection for community land rights. However, PTSL data management in Bukur Village is still carried out manually using physical documents and Microsoft Excel, potentially causing process delays, data duplication, and file loss. This study aims to develop a website-based PTSL information system to improve the efficiency and transparency of land data management. The study used the Extreme Programming (XP) software development method, which includes iterative planning, design, coding, and testing stages. Data were collected through observation, interviews, and documentation. The system was developed using the Laravel framework, a MySQL database, and Leaflet-based Geographic Information System (GIS) integration to visualize land locations. System testing was conducted using Black Box Testing on 15 test scenarios that included authentication, file management, document upload, status monitoring, data export, and map visualization. The test results showed that all 15 scenarios were successfully executed according to the expected output with a 100% success rate. The developed system is able to integrate applicant and file data management, support application status monitoring, and present land location information visually. Thus, this website-based PTSL information system can be a solution to increase efficiency, reduce the risk of data management errors, and facilitate access to land information for admins and the public.